Project based learning model - Eco pedagogy on environmental health material in public junior high schools in Sukoharjo regency - Rohsulina, Pranichayudha; Setyowati, Dewi Liesnoor; Priyanto, Agustinus Sugeng; Utomo, Cahyo Budi (Edelweiss Applied Science and Technology, 2024)
The application of the Project Based Learning – Ecopedagogy learning model in learning is expected to change students’ ecological intelligence to improve environmental health problems by providing knowledge to change attitudes and improve skills regarding the environment. This study aims to analyze the implementation of the independent curriculum and compile and analyze the performance and effectiveness of the Project Based Learning (PjBL) – Ecopedagogy Model in junior high schools throughout Sukoharjo Regency. The researcher uses the research and development (R&D) method; the researcher will develop a product as a social studies learning design, namely the Project Based Learning – Ecopedagogy Model in junior high schools throughout the Regency. The researcher then tested the data that had been obtained using the data triangulation method. Data analysis in this study used qualitative and quantitative descriptive analysis techniques. The results of this study are the results of data recapitulation which show that 84% of junior high schools have implemented student understanding of the independent curriculum. The PjBL learning model shows that it can influence the increase in student activity in learning about health.